Sistem Infromasi Akuntansi Kas Kecil Pada PT. Zokkas Sejahtera Jambi - Wahyu Dewanto; Rolyna Simbolon (Journal of Applied Accounting and Business, 2020)
PT Zokkas Sejahtera Jambi, located in Telanaipura, Jambi City, is a company engaged in the distribution sector to various locations, supermarkets, minimarkets and pharmacies with products sold such as Madurasa, soap, hand body, and other types of goods. The management of petty cash data and at PT Zokkas Sejahtera Jambi is still manual so that the performance of the petty cash recording process is not optimal. So we need a web-based antansi information system. This research was conducted at PT Zokkas Sejahtera Jambi, the petty cash accounting information system at PT Zokkas Sejahtera Jambi using the fluctuation method or the method of changing funds. Every time a petty cash transaction occurs, it is immediately recorded. The methods used by the author are data collection techniques, development of petty cash accounting information systems and the waterfall method, system design and data flow models used are DFD (Data Flow Diagram), programming language using PHP, and the MySQL database. This research produces a web-based application that is equipped with printed petty cash reports, petty cash transactions, and ledgers. This research produces a petty cash accounting information system that can be implemented at PT Zokkas Sejahtera Jambi.